2012
DOI: 10.1208/s12249-012-9818-z
|View full text |Cite
|
Sign up to set email alerts
|

The Stokes Number Approach to Support Scale-Up and Technology Transfer of a Mixing Process

Abstract: Abstract. Transferring processes between different scales and types of mixers is a common operation in industry. Challenges within this operation include the existence of considerable differences in blending conditions between mixer scales and types. Obtaining the correct blending conditions is crucial for the ability to break up agglomerates in order to achieve the desired blend uniformity. Agglomerate break up is often an abrasion process. In this study, the abrasion rate potential of agglomerates is describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Powder surface velocities observed by the camera (v p. ) at different fill volumes (φ) and container rotational speeds (ω) (experimental: white diamonds: φ040% (V/V), ω020 RPM; white squares: φ 040% (V/V), ω 030 RPM; white triangles: φ 040% (V/V), ω 0 40 RPM; X marks: φ053% (V/V), ω040 RPM; asterisks: φ067% (V/V), ω040 RPM; white circles: φ080% (V/V), ω040 RPM). Velocity of cascading layer obtained by DEM calculations: black circles: φ040% (V/V), ω0 40 RPM Our previous work showed that filler powder velocity is an important parameter in relation to the abrasion rate constant of agglomerates (8,19). For this reason, the following step is to evaluate effects of the speed of the cascading layer on the abrasion rate constants of agglomerates.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Powder surface velocities observed by the camera (v p. ) at different fill volumes (φ) and container rotational speeds (ω) (experimental: white diamonds: φ040% (V/V), ω020 RPM; white squares: φ 040% (V/V), ω 030 RPM; white triangles: φ 040% (V/V), ω 0 40 RPM; X marks: φ053% (V/V), ω040 RPM; asterisks: φ067% (V/V), ω040 RPM; white circles: φ080% (V/V), ω040 RPM). Velocity of cascading layer obtained by DEM calculations: black circles: φ040% (V/V), ω0 40 RPM Our previous work showed that filler powder velocity is an important parameter in relation to the abrasion rate constant of agglomerates (8,19). For this reason, the following step is to evaluate effects of the speed of the cascading layer on the abrasion rate constants of agglomerates.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…These effects are correlated using the Stokes abrasion number (St Abr ). The Stokes abrasion number concept has been discussed earlier in more detail in previous papers (9,19):…”
Section: Powder Surface Velocity and Stokes Abrasion Number (St Abr )mentioning
confidence: 99%
“…The effects of the mixer rotation speed and the mixer size on abrasion were consistent with experiments . In addition, it was found that the Stoke number, defined as the ratio between the kinetic energy density of a powder bed and work of fracture of an agglomerate, was proportional to the abrasion rate, as observed in the experiments …”
Section: Introductionmentioning
confidence: 99%